Christmas Streak 28/88: Similar But Different

Calculus Level 5

Define P \mathbb{P} as the set of positive reals, and R \mathbb{R} as the set of reals.

Two functions f : P R f^-:\mathbb{P}\to\mathbb{R} and f + : P R f^+:\mathbb{P}\to\mathbb{R} both have their second derivatives well-defined in their domains.

{ f ( x ) = ( x 1 ) e x 1 + 1 x 2 t f ( t ) t d t ; f + ( x ) = ( x 1 ) e x 1 + 1 x 2 t + f + ( t ) t d t . \cases{\displaystyle f^-(x)=(x-1)e^{x-1}+\int_{1}^{x}\frac{2t-f^-(t)}{t}dt; \\\\ \displaystyle f^+(x)=(x-1)e^{x-1}+\int_{1}^{x} \frac{2t+f^+(t)}{t}dt.}

f + ( 2 ) + f ( 2 ) = a e + ln b + c , f^+(2)+f^-(2)=a\cdot e+\ln b+c, for some integers a , b a,~b and c . c. Find the value of a 3 + b 3 + c 3 . a^3+b^3+c^3.


This problem is a part of <Christmas Streak 2017> series .


The answer is 4122.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Boi (보이)
Oct 26, 2017

Let f = g f^-=g and f + = h f^+=h for clarity.

g ( x ) = ( x 1 ) e x 1 + 1 x 2 t g ( t ) t d t \displaystyle g(x)=(x-1)e^{x-1}+\int_{1}^{x} \frac{2t-g(t)}{t}dt

From this we see that g ( 1 ) = 0. g(1)=0. Differentiate both sides with respect to x . x.

g ( x ) = x e x 1 + 2 x g ( x ) x g'(x)=xe^{x-1}+\dfrac{2x-g(x)}{x}

x g ( x ) = x 2 e x 1 + 2 x g ( x ) xg'(x)=x^2e^{x-1}+2x-g(x)

x g ( x ) + g ( x ) = x 2 e x 1 + 2 x xg'(x)+g(x)=x^2e^{x-1}+2x

Integrate both sides, using the fact that ( x g ( x ) ) = x g ( x ) + g ( x ) . (xg(x))'=xg'(x)+g(x).

x g ( x ) = ( x 2 2 x + 2 ) e x 1 + x 2 + C 1 xg(x)=(x^2-2x+2)e^{x-1}+x^2+C_1

Now substitute x = 1 x=1 and use that g ( 1 ) = 0. C 1 = 2. g(1)=0.~\Rightarrow~C_1=-2.

Therefore x g ( x ) = ( x 2 2 x + 2 ) e x 1 + x 2 2. xg(x)=(x^2-2x+2)e^{x-1}+x^2-2.

g ( x ) = x 2 2 x + 2 x e x 1 + x 2 x . \therefore~g(x)=\dfrac{x^2-2x+2}{x}e^{x-1}+x-\dfrac{2}{x}.


h ( x ) = ( x 1 ) e x 1 + 1 x 2 t + h ( t ) t d t \displaystyle h(x)=(x-1)e^{x-1}+\int_{1}^{x} \frac{2t+h(t)}{t}dt

From this we see that h ( 1 ) = 0. h(1)=0. Differentiate both sides with respect to x . x.

h ( x ) = x e x 1 + 2 x + h ( x ) x h'(x)=xe^{x-1}+\dfrac{2x+h(x)}{x}

x h ( x ) = x 2 e x 1 + 2 x + h ( x ) xh'(x)=x^2e^{x-1}+2x+h(x)

What's different here is that we'll differentiate both sides this time.

Before doing that, substitute x = 1 x=1 and notice that h ( 1 ) = 3 + h ( 1 ) = 3. h'(1)=3+h(1)=3.

x h ( x ) + h ( x ) = ( x 2 + 2 x ) e x 1 + 2 + h ( x ) xh''(x)+h'(x)=(x^2+2x)e^{x-1}+2+h'(x)

h ( x ) = ( x + 2 ) e x 1 + 2 x h''(x)=(x+2)e^{x-1}+\dfrac{2}{x}

Integrate both sides.

h ( x ) = ( x + 1 ) e x 1 + 2 ln x + C 2 h'(x)=(x+1)e^{x-1}+2\ln x + C_2

Substitute x = 1 x=1 and use that h ( 1 ) = 3. C 2 = 1. h'(1)=3.~\Rightarrow~C_2=1.

Integrate again to get h ( x ) = x e x 1 + 2 x ( ln x 1 ) + x + C 3 . h(x)=xe^{x-1}+2x(\ln x -1)+x+C_3.

Substitute x = 1 x=1 and use that h ( 1 ) = 0. C 3 = 0. h(1)=0.~\Rightarrow~C_3=0.

h ( x ) = x e x 1 + 2 x ln x x . \therefore~h(x)=xe^{x-1}+2x\ln x - x.


From above, we see that g ( 2 ) + h ( 2 ) = ( e + 1 ) + ( 2 e + 4 ln 2 2 ) = 3 e + ln 16 1. g(2)+h(2)=(e+1)+(2e+4\ln 2-2)=3e+\ln 16 - 1.

a 3 + b 3 + c 3 = 3 3 + 1 6 3 + ( 1 ) 3 = 4122 . \therefore~a^3+b^3+c^3=3^3+16^3+(-1)^3=\boxed{4122}.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...